PENGARUH JOB SATISFACTION, JOB EMBEDDEDNESS, DAN BEBAN KERJA TERHADAP TURNOVER INTENTION PADA PEKERJA DIVISI MARKETING PT MUSAWA LAND DI KOTA SEMARANG - Dysta Shafira Oktaviani; Ratih Hesty Utami; Qristin Violinda (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to determine what factors influence Turnover Intention in Marketing Division employees at PT Musawa Land in Semarang City. The population used in this study are all marketing division imployess in the PT Musawa Land and the sample used is 112 employees with the slovin formula, using a probability sampling technique with a random sampling method. Data analysis in this study used the SPSS 24 program. Testing the hypothesis with a multiple linear regression approach. The results of the analysis and discussion show that the variables have a partial effect, namely; Job Satisfaction has a negative and significant effect on Turnover Intention, Job Embeddedness has a negative and significant effect on Turnover Intention, Workload has a positive and significant effect on Turnover Intention for Marketing Division employees at PT Musawa Land in Semarang City.